Underwater Particle Image Velocimetry (PIV) Measurement of Turbulence Over Mussel Bed in a Deepsite of Lake Michigan - (:unkn) unknown (My University, 2019)
The influence of the benthic filter feeders, such as bivalves, on ecosystem plankton, and nutrient dynamics is considered significant in shallow marine and freshwater systems. Recent indirect evidence showed that the profundal quagga mussels (Dreissena rostriformis bugensis) have fundamentally altered energy flow and dynamics of nutrients and phytoplankton in Lake Michigan and other Great Lakes. To investigate the phytoplankton grazing rate of the quagga mussel and the mussel siphon currents induced bio-mixing, a self-contained in situ Underwater Particle Image Velocimetry was developed to measure the turbulence structure and the turbulent diffusion coefficient immediately above the profundal quagga mussel covered substrate in the deep-water site located in Lake Michigan. The system was deployed from July to October 2018, and 500 sets of datasets were acquired with 400 snaps of 2D velocity and particle concentration maps for each set. The diffusion coefficients were estimated and compared from multiple methods with measurements of turbulence and particle density. Field data analysis suggested that in the low energetic deep lake benthic boundary, mussels’ siphon currents are the major source of turbulence. Turbulent diffusivity/viscosity varied between 10-6 to 10-5 (m2 s-1), which seemed to correlate with the ambient particle concentration. Collective pumping rates of mussels were also estimated from measured near-bed turbulent flux of particles. Data also showed that near-bed turbulent diffusivity increases linearly with mussels’ pumping rate. This empirical linear relation was applied to a one-D numerical model. Simulation results proved the hypothesis that profundal mussels can maximize their grazing efficiently by the enhanced near-bed turbulence due to siphon currents. Modeling simulation also suggested that an optimal collective pumping rate may exist, which varied between about 1 to 5 liters per day per individual, depending on the ambient mixing condition.
Keywords: Diffusivity; Numerical Modeling; PIV; Quagga mussel; TKE; Turbulence